The Patterns of Music Learning in Phenomena of Valerio International Guitar Festival - Walidaini, Birul; Sayuti, Suminto A; Pradoko, AM Susilo (Harmonia: Journal of Arts Research and Education, 2022)
This study aims to reveal the finalists’ learning patterns and outcomes at the 2018 Valerio International Guitar Festival. It is qualitative research with the phenomenological approach. It was conducted in the final round of the open category of the 2018 Valerio International Guitar Festival. The informants in this study include the finalists, judges, and organizers. The data were obtained through observation, interviews, and documentation studies. The research findings show that the music learning process among the finalists of the 2018 Valerio International Guitar Festival is carried out through lectures (formal), courses (non-formal), and community (non-formal). The learning patterns experienced by the finalists have shaped the competitive mentality of the finalists of the 2018 Valerio International Guitar Festival. The competitive mentality formed includes: (1) increasing repertoire mastery which reflects independence in achieving the target of mastery of the chosen repertoire that will be performed; and (2) the mentality to perform on stage in the competition arena. In this mentality, the finalists have high motivation when performing on the stage. The motivation that grows comes from within and outside the finalists. In addition, the finalists also have the mentality to be ready to face various possibilities that will be experienced, both in terms of musical and non-musical abilities, such as how to use the right strategy when facing the audience and maintain calm while playing.